Threatened and endemic seed plants of Mt. Pantaron Range, Mindanao, Philippines - Curitico, Fulgent P.; Legaspi, Mutya L.; Lagunday, Noel E.; Guiang, Maria Melanie M.; Tandang, Danilo N.; Gulindon, John Michael M.; Acma, Florfe M.; Amorsolo, Victor B. (2022)
Mt. Pantaron Range has no legislation for its protection and has significantly lost moss of its forest cover over the years due to land conversion for agriculture and human settlement, construction of national highways, and illegal logging and mining. Floristic inventory was conducted in four sampling sites in Mt. Pantaron Range, Bukidnon to document its threatened and endemic seed plants through repeated repeated walks. A total of 133 threatened and endemic species of seed plants were documented. Of these, 41 species were threatened and 120 were endemic species. Mt. Bungkasan, Pantaron Range harbors 70 (56.6%) species of threatened and endemic seed plants.
Keywords: Endemic plants